Knowledge of ovarian cancer and its determinants factors among women attending clinic in Hospital USM - Hashim, Norhazliana (2020)
Ovarian Cancer is known as the fourth leading cancer in Malaysia. A cross sectional study was conducted on 110 women attending clinic in Hospital USM. The general objective of the study was to determine the knowledge level of ovarian cancer and its determinants factors among women attending clinic in Hospital USM. Respondents were recruited using a non-probability purposive sampling method. Demographic data of the respondents was analysed using descriptive statistic. Descriptive statistic was also used to determine the level of knowledge of ovarian cancer among women attending clinic in Hospital USM. A validated questionnaire was given to all respondent that fit the inclusion criteria Pearson’s Chi Square test was applied to study the relationship between level of knowledge on ovarian cancer with selected factors (age, marital status, educational level, hear/read about ovarian cancer, interest to know about ovarian cancer, has family history of ovarian cancer, had discuss about ovarian cancer with doctor). The findings of this study show that majority of women has low knowledge on ovarian cancer. In this study, there is no statistically significant relationship between selected factors (age, marital status, educational level, hear/read about ovarian cancer, interest to know about ovarian cancer, had family history of ovarian cancer, had discuss about ovarian cancer with doctor) with knowledge level of ovarian cancer. By increasing knowledge on ovarian cancer among women might help in reducing the mortality rate among women.